sp[Î³,Î³^(* ) ]-open sets and sp[Î³,Î³^(* ) ]-compact spaces - Jamil, Jamil Mahmoud (Iraqi Journal of Science, 2020)
In this work, we present the notion of sp[Î³,Î³^(* ) ]-open set, sp[Î³,Î³^(* ) ]-closed, and sp[Î³,Î³^(* ) ]-closure such that several properties are obtained. By using this concept, we define a new type of spaces named sp[Î³,Î³^(* ) ]-compact space.